Users’ forest experience at Sungai Kanching Recreational Forest, Selangor / Marzila Aziz and Nur Idzhainee Hashim - Aziz, Marzila; Hashim, Nur Idzhainee (2018)
Visiting forest for recreational experiences has risen as one of the most popular tourism activities worldwide. Many scholars make an inference that recreation is an emotionally transforming activity designed to meet personal needs and motivations. Viewing a forest scene has been documented to have a positive effect on psychological healing and well-being in terms of recovering from stress, improving concentration and productivity, cultivating the psychological state, especially for urbanites. Nevertheless, occasionally there are several factors that contribute to the unsuccessful achievements of the superlative experience such as natural threat, damaged, inadequate facilities and unpleasant environment at the recreational forest. This study is a concept paper that aims to identify users’ forest experience at Sungai Kanching Recreational Forest, Selangor. The findings of this study have identified three elements of forest experience which are transcendent experience, restorative experience and flow experience that can be achieved by the users. Consequently, this study will help stakeholders to provide proper management in order for recreational user’s to gain preeminent experience at the recreational forest in Malaysia.